Neurophysiological and Behavioral Differences between Older and Younger Adults When Processing Violations of Tonal Structure in Music - Lagrois, Marie-Élaine; Peretz, Isabelle; Zendel, Benjamin Rich (Frontiers in Neuroscience, 2018)
Aging is associated with decline in both cognitive and auditory abilities. However, evidence suggests that music perception is relatively spared, despite relying on auditory and cognitive abilities that tend to decline with age. It is therefore likely that older adults engage compensatory mechanisms which should be evident in the underlying functional neurophysiology related to processing music. In other words, the perception of musical structure would be similar or enhanced in older compared to younger adults, while the underlying functional neurophysiology would be different. The present study aimed to compare the electrophysiological brain responses of younger and older adults to melodic incongruities during a passive and active listening task. Older and younger adults had a similar ability to detect an out-of-tune incongruity (i.e. non-chromatic), while the amplitudes of the ERAN and P600 were reduced in older adults compared to younger adults. On the other hand, out-of-key incongruities (i.e., non-diatonic), were better detected by older adults compared to younger adults, while the ERAN and P600 were comparable between the two age groups. This pattern of results indicates that perception of tonal structure is preserved in older adults, despite age-related neurophysiological changes in how melodic violations are processed.